An autonomous restaurant service robot with high positioning accuracy - Yu, Qingxiao; Yuan, Can; Fu, Z.; Zhao, Yanzheng (Industrial robot, 2012)
Purpose - Recently, service robots have been widely used in various fields. The purpose of this paper is to design a restaurant service robot which could be applicable to provide basic service, such as ordering, fetching and sending food, settlement and so on, for the customers in the robot restaurant.Design methodology approach - Based on characteristics of wheeled mobile robots, the service robot with two manipulators is designed. Constrained by the DOF, the final positioning accuracy within ±3 cm must be guaranteed to successfully grasp the plate. Segmented positioning method is applied considering the positioning costs and accuracy requirement in the different stages, and the shape-based matching tracking method is adopted to navigate the robot to the object.Findings - Experiments indicate that the service robot could successfully grasp the plate, from wherever is its initial position; and the proposed algorithms could estimate the robot pose well and accurately evaluate the localization performance.Research limitations implications - At present, the service robot could only work in an indoor environment where there is steady illumination.Practical implications - The service robot is applicable to provide basic service for the customers in the robot restaurant.Originality value - The paper gives us a concept of a restaurant service robot and its localization and navigation algorithms. The service robot could provide its real-time coordinates and arrive at the object with ±2 cm positioning precision, from wherever is its initial position.